The Gendered Politics of Pandemic Relief: Labor and Family Policies in Denmark, Germany, and the United States During COVID-19 - Bariola, Nino; Collins, Caitlyn (The American behavioral scientist (Beverly Hills), 2021)
The COVID-19 pandemic has magnified families’ struggles to reconcile caregiving and employment, especially for working mothers. How have different countries reacted to these troubling circumstances? What policies have been implemented to alleviate the pernicious effects of the pandemic on gender and labor inequalities? We examine the policies offered in Denmark, Germany, and the United States, three countries that represent distinct welfare regimes. We find important differences among the policy solutions provided, but also in the “cultural infrastructures” that allow policies to work as intended, or not. In Denmark, a social-democratic welfare state, robust federal salary guarantee programs supplemented an already strong social safety net. The country was among the first to lock down and reorganize health care—and also among the first to reopen schools and child care facilities, acknowledging that parents’ employment depends on child care provisioning, especially for mothers. Germany, a corporatist regime, substantially expanded existing programs and provided generous subsidies. However, despite an ongoing official commitment to reduce gender inequality, the cultural legacy of a father breadwinner/mother caregiver family model meant that reopening child care facilities was not a first priority, which pushed many mothers out of paid work. In the U.S. liberal regime, private organizations—particularly in privileged economic sectors—are the ones primarily offering supports to working parents. Patchwork efforts at lockdown and reopening have meant a lengthy period of limbo for working families, with disastrous consequences for women, especially the most vulnerable. Among such varied “solutions” to the consequences of the pandemic, those of liberal regimes seem to be worsening inequalities. The unprecedented nature of the current pandemic recession suggests a need for scholars to gender the study of economic crises.